2020
DOI: 10.1002/jlb.3a0720-422r
|View full text |Cite
|
Sign up to set email alerts
|

Different glycoforms of alpha-1-acid glycoprotein contribute to its functional alterations in platelets and neutrophils

Abstract: Alpha-1-acid glycoprotein (AGP-1) is a positive acute phase glycoprotein with uncertain functions.Serum AGP-1 (sAGP-1) is primarily derived from hepatocytes and circulates as 12-20 different glycoforms. We isolated a glycoform secreted from platelet-activating factor (PAF)-stimulated human neutrophils (nAGP-1). Its peptide sequence was identical to hepatocyte-derived sAGP-1, but nAGP-1 differed from sAGP-1 in its chromatographic behavior, electrophoretic mobility, and pattern of glycosylation. The function of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 81 publications
(165 reference statements)
0
14
0
Order By: Relevance
“…17 Moreover, different glycoforms of AGP1 affect the activity of platelets and neutrophils in acute inflammation. 18 The abnormal expression of AGP1 was found to be associated with cardiovascular diseases, 19 primary aldosteronism, 20 and tumorigenesis of cancers. 21 Recently, more evidence has demonstrated that AGP1 could be a diagnostic or prognostic biomarker in tumors such as laryngeal 17 and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, different glycoforms of AGP1 affect the activity of platelets and neutrophils in acute inflammation. 18 The abnormal expression of AGP1 was found to be associated with cardiovascular diseases, 19 primary aldosteronism, 20 and tumorigenesis of cancers. 21 Recently, more evidence has demonstrated that AGP1 could be a diagnostic or prognostic biomarker in tumors such as laryngeal 17 and pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in addition to the liver, AGP-1 is expressed by activated neutrophils. In contrast to the N-glycans expressed on hepatic AGP-1 (hAGP-1), neutrophil-expressed AGP-1 (nAGP-1) carries mainly high-mannose, nonsialylated, and mono-sialylated N-glycans ( 76 ). Taken together, these data may indicate that chronic inflammation in some cases attenuates neutrophil recruitment and activation in favor of other, more potent leukocytes.…”
Section: Innate Immunitymentioning
confidence: 99%
“…At present, it has been confirmed that there are five N-glycosylation sites in AGP, which is a complex N-glycan and can form various types of branched conformations of sugar chains, with approximately 11% of the N-glycan chains undergoing sialylation [ 136 ]. It has been documented that the glycan conformation of AGP and other modification types on its N-glycan chain are highly correlated with the disease stage, and the level of N-glycan modification of AGP varies among different cancer types [ 137 ]. AGP can be used together with other marker proteins for the clinical diagnosis of liver cancer.…”
Section: Introductionmentioning
confidence: 99%